Primary Hepatic Leiomyoma in a Healthy Middle-Aged Woman: Literature Review and Case Report - Djokic, Mihajlo; Hadzialjevic, Benjamin; Luzar, Bostjan; Trotovsek, Blaz (Frontiers in Surgery, 2021)
Introduction: Primary hepatic leiomyoma (PHL) is a rare benign hepatic tumor with unclear pathogenesis. It more commonly occurs in immunosuppressed patients, while only 24 cases have been described among immunocompetent individuals. To date, only one successful preoperative diagnosis of PHL has been achieved. Case presentation: Here we report a case of PHL in a middle-aged woman with no history of immunosuppression. Preoperative diagnosis of PHL was established using ultrasound-guided fine needle trucut biopsy (FNTB). Nevertheless, due to the growing nature of tumor and patient’s symptoms, we proceeded with surgical resection, which confirmed the diagnosis of PHL. At 6-month follow up, the patient is in good condition with no evidence of tumor recurrence. Conclusions: PHL is an uncommon tumor that should be considered in the differential diagnosis of rare liver tumors. Image guided FNTB appears to be effective in achieving preoperative diagnosis of PHL. Surgical resection, however, remains both diagnostic and curative in the management of PHL.